PENEGAKAN HUKUM TERHADAP PELAKU USAHA YANG TIDAK MEMENUHI STANDAR PROTOKOL KESEHATAN COVID-19 MENURUT PERATURAN WALI KOTA SURABAYA NOMOR 10 TAHUN 2021 - Fajar Maoke Subroto; Sugeng Hadi Purnomo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
Various strategic steps have been taken by the Surabaya city government to suppress the spread of the deltacron variant of Covid-19 both in the issuance of individual and business actor regulations. The regulation is in the form of Surabaya Mayor Regulation Number 10 of 2021 concerning the implementation of health protocols in order to prevent and break the chain of spread of Covid-19 in the city of Surabaya. However, there are still many business actors in the city of Surabaya who do not comply with and implement health protocols in accordance with the Mayor's Regulation. The formulation discussed in this study is how law enforcement against business actors according to Surabaya Mayor Regulation Number 10 of 2021 and what are the obstacles in law enforcement against business actors according to Surabaya Mayor Regulation Number 10 of 2021. The research method used in this study is a normative juridical research method using a qualitative approach. The result of this study was the business actor Warkop S who violated article 7 paragraphs 2 and 3 with administrative sanctions in the form of an administrative fine of Rp. 500,000.00 (five hundred thousand rupiah), the manager of the Escobar discotheque violated article 32 with administrative sanctions in the form of revoking the tourism business register license and the manager of the Tunjungan Plaza Surabaya shopping center violated article 7 paragraph 11 with administrative sanctions in the form of a written reprimand and an administrative fine of Rp. 25,000,000.00 (twenty-five million rupiah). The obstacles in law enforcement in this Mayor's Regulation are the lack of awareness of business actors and economic reasons